Positive deviance and Islamic leadership - Fontaine, Rodrigue Ancelot Harvey (International Islamic University, 2011)
This study investigates whether positive deviance can become a tool to promote leadership from an Islamic perspective. This study offers a brief review of the literature on leadership, the link between perception and leadership and leadership from an Islamic perspective. In particular, attention is drawn to the work of Beekun and Badawi (1999) in the area of leadership from an Islamic perspective. This author suggests that practitioners find it difficult to implement principles of Islamic leadership because they lack specific management tools. By reviewing the literature, this author has identified positive deviance as a management tool for leaders to challenge and change the collective perceptions of followers. Within this context, the positive deviance methodology fits in remarkably well with the framework proposed by Beekun and Badawi (1999). The suitability of positive deviance as a tool for Islamic leaders is explored.